A constituição da identidade linguística surda: a narrativização avaliativa surda sobre Língua Portuguesa e Libras - ARAÚJO, Marília do Socorro Oliveira (Universidade Federal do Pará, 2021)
This article intends to discuss and bring up ideas for the development of a historical-critical materialist pedagogy within the Portuguese language classes, emphasizing questions and activities to be developed in Elementary School, but which can be applied with variations in other grades too. The texts chosen for analysis and development of the didactic sequence were A Festa no Céu (The party in the Sky), a traditional Brazilian tale narrated by Luís Câmara Cascudo andThe fox and the grapes, one of Aesop's fables. Thus we intend to contribute to the teaching of Portuguese language in Brazil and with the literature`s teaching in Latin American`s Elementary School, reflecting the voices of a pedagogy focused on humanization, critical thinking and reflection on the reality that surrounds us. For this study, we used the theoretical contributions of Labov (1997), Barthes (1976) e Fiorin (2008).